2013
DOI: 10.5755/j01.ms.19.3.1397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatments on the Microstructure, Hardness and Corrosion Behavior of Nondendritic AlSi9Cu3(Fe) Cast Alloy

Abstract: In this paper we studied the influence of heat treatments on properties of AlSi9Cu3(Fe) nondendritic cast alloy. Solution heat treatment, six hours at 520 °C, while making the grains more spherical modifies corrosion morphology into intergranular corrosion and corrosion surrounding spherical particles in 3 % NaCl solution. Past solution treatment, quenching at 520 °C after one hour with two weeks of natural aging transform the shape of grains into equiaxes form. Two weeks of natural aging and 30 minutes of agi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
(24 reference statements)
2
3
0
Order By: Relevance
“…The distribution of Si is not close to any element (except in some places where it coincides with Fe, Mn, and Cr), which indicates the presence of eutectic Si particles. So, according to the results obtained and in agreement with the literature, the formation of Al 2 Cu and various Fe-containing phases (AlFeSi, Al(Fe,Mn,Cr)Si) with Si is possible [37][38][39][40][41]. The greatest surface damage has been observed in the vicinity of intermetallic phases rich in Cu and Fe, which is associated with a higher oxygen content (i.e., the formation of Al 2 O 3 due to the Al dissolution).…”
Section: Surface Analysis After Corrosion Measurementssupporting
confidence: 90%
See 2 more Smart Citations
“…The distribution of Si is not close to any element (except in some places where it coincides with Fe, Mn, and Cr), which indicates the presence of eutectic Si particles. So, according to the results obtained and in agreement with the literature, the formation of Al 2 Cu and various Fe-containing phases (AlFeSi, Al(Fe,Mn,Cr)Si) with Si is possible [37][38][39][40][41]. The greatest surface damage has been observed in the vicinity of intermetallic phases rich in Cu and Fe, which is associated with a higher oxygen content (i.e., the formation of Al 2 O 3 due to the Al dissolution).…”
Section: Surface Analysis After Corrosion Measurementssupporting
confidence: 90%
“…They found that corrosion starts at the interface between the α-Al matrix and the Fe-rich IMCs due to microgalvanic corrosion processes. A similar influence of IMCs on the localised forms of corrosion of Al alloys was observed by Akiyama et al [38], Brunner et al [39], and Zazi [40]. Monticelli et al [41] point out that the potential differences between IMCs and the α-Al matrix in the AlSi9Cu3(Fe) alloy can reach up to 400 mV, leading to an intense corrosion attack and localised corrosion forms.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, they cannot be used for other applications like safety relevant structural pieces, because of the difficult removal of iron and copper during the recycling of scrap that causes a decrease of the final component's properties. [11] In detail, the presence of β-iron precipitates causes a very low ductility, not acceptable for these classes of components. In addition, either iron or copper precipitates strongly reduces corrosion resistance that is another fundamental item required in this field.…”
Section: Introductionmentioning
confidence: 99%
“…The α-aluminum phase represents the matrix of cast aluminum-silicon alloys; it crystallizes in the appearance of non-faceted dendrites (Warmuzek 2004), and sometimes in appearance of non-dendritic forms (Zazi 2013). Moreover, the hard primary silicon particles distributed in the matrix are responsible for the good mechanical properties and the high wear resistance (Elzanaty 2015).…”
Section: Introductionmentioning
confidence: 99%